2020
DOI: 10.35631//jthem.518007
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Supportive Management and Employees’ Commitment to Service Quality Towards Service Recovery Performance Among Hotel Employees in Malaysia

Abstract: Service recovery performance is highly significant in the hotel sector as it ensures customers’ satisfaction and loyalty. Long and inconsistent working hours and schedules, along with strenuous tasks, are the norm for jobs in the hotel sector and these challenging traits can greatly effect the job performance of hotel employees. Hence it is fundamental to identify the factors affecting their performance of service recovery. In developed countries, a large number of studies have been reported on service recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…That is to say, those with a high behavioral CQ can quickly adapt to another's gestures to enable a pleasant intercultural conversation. Aside from having the ability to adjust both verbal and nonverbal behavior for effective communication, an individual must also have a varied range of behaviors that can be deployed flexibly in response to a variety of challenging situations [21,81]. Individuals with high behavioral CQ also understand how to employ culturally appropriate vocabulary, tone, gestures, and facial expressions [21].…”
Section: Discussionmentioning
confidence: 99%
“…That is to say, those with a high behavioral CQ can quickly adapt to another's gestures to enable a pleasant intercultural conversation. Aside from having the ability to adjust both verbal and nonverbal behavior for effective communication, an individual must also have a varied range of behaviors that can be deployed flexibly in response to a variety of challenging situations [21,81]. Individuals with high behavioral CQ also understand how to employ culturally appropriate vocabulary, tone, gestures, and facial expressions [21].…”
Section: Discussionmentioning
confidence: 99%
“…Past research has proved that employees' commitment is essential for the hotel industry as more the employees are committed, less is their turnover intention (Mousa, 2021; Yao et al ., 2019). Past research has identified various factors that either leads to or lead by the (AOC) such as personality traits, direct intrinsic motivation, training and development and organizational commitment (Chew and Wong, 2008; Choong et al ., 2011; Farrukh et al ., 2017; Rosli and Zainal, 2019). Interestingly till date no research has explored the component of employees' PCA in creating AOC in the hotel industry of Malaysia.…”
Section: Introductionmentioning
confidence: 99%